Academic resilience pada siswa Sekolah Menengah Kejuruan (SMK): Menguji peranan problem focused coping - Handy Wiranto; Karolin Rista; Suroso (INNER: Journal of Psychological Research, 2022)
Abstract This research was conducted based on the phenomenon of students in the inability to bounce back after facing problems at school. Academic resilience is the ability to quickly recover from changes, challenges, and difficulties in finding solutions. This study aims to determine the relationship between problem focused coping and academic resilience in students at SMK Plus Nu Sidoarjo. This study uses a correlational quantitative design. The number of subjects in this study were 81 students who were selected using simple random sampling technique. The measuring instruments used are the problem focused coping scale and the academic resilience scale which the researchers compiled the mselves. The reliability coefficient of the problem focused coping scale is 0.841, and the reliability coefficient of the academic resilience scale is 0.873. Based on the results of the Spearman Rho correlation coefficient analysis, the correlation coefficient value (R) was 0.544 with a p significance of 0.000 (p <0.05). Thus, the hypothesis is accepted. That is, the higher the problem focused coping , the higher the academic resilience , and vice versa, the lower the problem focused coping , the lower the academic resilience. Keywords : Problem Focused Coping, Academic Resilience, academic problem